Barking up the wrong tree : the surprising science behind why everything you know about success is (mostly) wrong - Barker, Eric. (New York : Harper One, 2017)
New York Times bestselling author Jenn McKinlay returns to Bluff Point, Maine, where one woman finds love with the help of an adorable golden retriever. LOVE IS A FOUR-LEGGED WORD. Carly DeCusati returned home to Bluff Point, Maine, with her tail between her legs. But she's determined to get her life back on track--and that means finding new homes for the elderly golden retriever and overly talkative parrot she inherited before her old life fell apart. Enter physical therapist and hot one-night stand James Sinclair. James doesn't care that Carly doesn't do relationships. He is determined to win her heart, promising to help her with the pets if she'll just give him the time of day. Carly agrees to date the irresistible James, and, for the first time in years, she's dreaming of a happily ever after. But James has secrets, and if he can't open up to Carly, their future could go to the dogs .
Includes reference.
Keywords: Dogs -- Fiction; Love stories; Romances